DEVELOPMENT OF COORDINATIONS TEST SYSTEM BASED ON ARDUINO - Adibil Mahdi Rahmad Hidayat; Yohandri Yohandri (PILLAR OF PHYSICS, 2021)
ABSTRACTIn sports activitiesaplaying tennis ball, a player will appear to haveagood coordination if he can move towards the ball while swinging his racket, then hit with the correct technique. At the moment, the catch and throw exercise is still counted manuallyowith the help of other people and is not veryieffective at doing it. catch is a test to determine the coordination between the eyes and hands using a tennisoball as a throw. The purpose of this study was to determine the performancetspecifications and designwspecifications of the Arduino-based fishing throwing tool to measure eye-handkcoordination. This re search includes engineering research. This study describes the performance specifications and designhspecifications of the catch and capture tool. The performance aspecification describes the function of the catch-and-catch tool builder, while the design specification describes the precision and precision of the tool. The measurement technique is carried out directly and iindirectly. Direct measurementscare made of the vibration and light intensity, while indirect measurements are carried out by analyzing the accuracy and accuracy of the catch and throw tool. The results of research on performance specifications and designuspecifications. First, the performance specification of the catch and catch device consists of an LDR sensor, a vibration sensor, and an electronic circuit that builds a catch-and-catch system. The secondaresult, the results of the design speccifications of this study consisted of the characterization of the tools and the accuracycof the catch and throw tool. The accuracy value of the catch throw tool is 100%.